Combined molecular and clinical assessment of Plasmodium falciparum antimalarial drug resistance in the Lao People's Democratic Republic (Laos) - Mayfong Mayxay (2018)
Molecular markers provide a rapid and relatively inexpensive approach for assessing antimalarial drug susceptibility. We collected 884 Plasmodium falciparum-infected blood samples from 17 Lao provinces. Each sample was genotyped for 11 codons in the chloroquine resistance transporter (pfcrt), dihydrofolate reductase (pfdhfr), and dihydropteroate synthase (pfdhps) genes. The samples included 227 collected from patients recruited to clinical trials. The pfcrt K76T mutation was an excellent predictor of treatment failure for both chloroquine and chloroquine plus sulfadoxine-pyrimethamine, and mutations in both pfdhfr and pfdhps were predictive of sulfadoxine-pyrimethamine treatment failure. In multivariate analysis, the presence of the pfdhfr triple mutation (51 + 59 + 108) was strongly and independently correlated with sulfadoxine-pyrimethamine failure (odds ratio = 9.1, 95% confidence interval = 1.4-60.2, P = 0.017). Considerable geographic heterogeneity in allele frequencies occurred at all three loci with lower frequencies of mutant alleles in southern than in northern Laos. These findings suggest that chloroquine and sulfadoxine-pyrimethamine are no longer viable therapy in this country. Copyright © 2007 by The American Society of Tropical Medicine and Hygiene.